Aortic Dissection Occurring 18 Months after Successful Endovascular Repair in an Anatomically Difficult Case of Abdominal Aortic Aneurysm - Satoshi Yamamoto; Katsuyuki Hoshina; Yutaka Takazawa; Hiroyuki Okamoto; Kunihiro Shigematsu; Tetsuro Miyata; Toshiaki Watanabe (Case Reports in Vascular Medicine)
We report an autopsy case of aneurysm dissection that occurred 18 months after the implantation of a Zenith stent graft. A 94-year-old woman, who had undergone an endovascular repair with postoperative reintervention, died of shock due to retroperitoneal hematoma. An autopsy indicated that the stent graft remained firmly fixed to the native aorta, whereas the dissection occurred near the proximal edge of the stent graft but not at the point of attachment between the suprarenal stent hook and the aorta. The luminal surface of the stent graft was almost completely covered with a transparent film with an endothelial cell lining, which might reflect the tissue regeneration observed on histological examination. This was a rare case of acute aortic dissection that occurred 18 months after EVAR, in which the autopsy indicated interesting microscopic findings and the mechanisms underlying the aortic dissection. We believe that aggressive reintervention at the proximal site in elderly women might cause the dissection of the native aorta.